Regulations of Gene Expression in Medullary Thymic Epithelial Cells Required for Preventing the Onset of Autoimmune Diseases - Akiyama, Taishin; Shinzawa, Miho; Qin, Junwen; Akiyama, Nobuko (Frontiers in Immunology, 2013)
Elimination of potential self-reactive T cells in the thymus is crucial for preventing the onset of autoimmune diseases. Epithelial cell subsets localized in thymic medulla (mTECs) contribute to this process by supplying a wide range of self-antigens that are otherwise expressed in a tissue-specific manner (TSAs). Expression of some TSAs in mTECs is controlled by the autoimmune regulator (AIRE) protein, of which dysfunctional mutations are the causative factor of autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy (APECED). In addition to the elimination of self-reactive T cells, recent studies indicated roles of mTECs in the development of Foxp3-positive regulatory T cells, which suppress autoimmunity and excess immune reactions in peripheral tissues. The TNF family cytokines, RANK ligand, CD40 ligand and lymphotoxin were found to promote the differentiation of AIRE- and TSA-expressing mTECs. Furthermore, activation of NF-κB is essential for mTEC differentiation. In this mini-review, we focus on molecular mechanisms that regulate induction of AIRE and TSA expression and discuss possible contributions of these mechanisms to prevent the onset of autoimmune diseases.